Transformational leadership and organizational commitment: Moderator role of pesantren employee job satisfaction - Busthomi Ibrahim; Abdul Rahim Zumrah; Supardi Supardi; Juhji Juhji (Institute of Advanced Engineering and Science, 2023)
This study aimed to determine the level of transformational leadership style, employee job satisfaction, and organizational commitment in pesantren (Islamic boarding school) and assess the role of job satisfaction as a mediator in the relationship between transformational leadership style and organizational commitment. The study used the quantitative method by surveying 556 educators from each Darunnajah Islamic boarding school branch in Indonesia. Information examination utilized numerous relapse investigation to test the inquire about theory and progressive relapse examination to test the intervention speculation. The study found that transformational authority, representative work fulfillment, and organizational commitment at Islamic boarding schools were more than direct. In expansion, representative work fulfillment can intercede between transformational authority and organizational commitment.